NEWS CONTENT ANALYSIS OF ANTARANEWS.COM ABOUT INDONESIA PRESIDENTIAL ELECTION 2014 - Ana Rosida (UIN Alauddin Makassar, 2017)
AbstractThe purpose of this thesis is to determine the tendency of news content attitude in presenting English news Antaranews.com about 2014 Indonesian presidential election, whether the result is neutral or not. In addition, the purpose of this thesis would also like to know what news topics are the most dominant in the presentation of 2014 Indonesian presidential election in this online media. This study analyzed 59 news about the presidential election during the campaign period that showed by Antaranews.com. This study used a descriptive method. It aims to describe to the reader and reveals a problem, situation, event as it is. This study involved two coders. Based on the analysis, the tendency news content attitude of Antaranews.com favoring the two candidates with the percentage, 36% pro Prabowo-Hatta and 37% pro Jokowi-JK. The most dominant news topic that showed in this Online Media is law and government with a percentage of 28%.AbstrakAnalisis Isi Berita Antaranews.com tentang Pemilihan Presiden tahun 2014. Tujuan dari skripsi ini adalah untuk mengetahui kecenderungan sikap isi berita berbahasa inggris Antaranews.com dalam menyajikan pemberitaan pemilihan presiden indonesia tahun 2014. Apakah hasilnya netral atau tidak. Selain itu, tujuan skripsi ini juga ingin mengetahui topik berita apa yang paling dominan dalam penyajian berita berbahasa inggris terkait Pemilihan Presiden Indonesia tahun 2014 pada media online tersebut. Penelitian ini menganalisis 59 berita tentang pemilihan presiden selama masa kampanye yang di tampilkan oleh Antaranews.com. Penelitian ini menggunakan metode deskriptif yang bertujuan untuk menggambarkan kepada pembaca dan mengungkapkan suatu masalah, keadaan, peristiwa sebagaimana adanya. Penelitian ini melibatkan dua coder. Berdasarkan hasil analisis, kecenderungan sikap isi berita Antaranews.com adalah memihak kepada dua kandidat dengan persentase, 36% pro Prabowo-Hatta dan 37% pro Jokowi-JK. Adapun topik berita yang paling dominan di tampilkan adalah hukum dan pemerintahan dengan persentase 28%.